Institutional Evaluation of the Indonesian Ombudsman Towards Effective, Inclusive, and Modern Public Service Oversight - Pambudi, Andi Setyo; Hidayat, Rahmat; Putri, Desak Made Annisa Cahya (Jambura Equilibrium Journal, 2026)
Quality of public services are the central pillar of creating good governance. In practice, problems such as maladministration, abuse of authority, corruption, and low transparency and accountability are still challenges in implementing public services. The Indonesian Ombudsman is the institution that has a strategic role in supervising public services in Indonesia. Nevertheless, the effectiveness of the Ombudsman in overseeing public service delivery in Indonesia faces numerous challenges, rendering its role less than optimal. This study aims to 1) analyze the effectiveness of the Ombudsman of the Republic of Indonesia in supervising public services; 2) analyze the current Ombudsman institution based on strengths, weaknesses, opportunities, and threats; and 3) formulate strategies and improve the effectiveness of Ombudsman supervision in the context of more effective, inclusive and modern public services. This study uses a qualitative approach with a descriptive-exploratory design based on literature studies and the analysis SWOT (Strengths, Weaknesses, Opportunities, and Threats) method. The results of this study indicate that it is necessary to carry out institutional reform of the Ombudsman, which includes the fulfillment of human resource support. The Ombudsman also needs to transform into a more modern institution that does not only act reactively to reports/complaints from the public that come to the Ombudsman but is also proactive in designing policies and recommendations.